STRUKTUR DAN MAKNA VISUAL IKLAN REJOICE EDISI RICH 3IN1 X KIKY SAPUTRI #RAMBUTNODRAMA - Ni Made Chandra Oktavia Devi (Warna Komunikasi, 2025)
Advertising is a type of information used to market goods to specific consumers. Every business must be able to produce eye-catching ads with a comprehensive visual structure that can be applied to current relevant media.  The shampoo product Rejoice is produced by PT. Procter & Gamble Operations Indonesia, which uses television and YouTube media to promote its products and collaborated with comedian Kiky Saputri who is famous for her roasting. The purpose of this research is to identify and analyze the Rejoice 3in1 x Kiky Saputri #RambutNoDrama Rich Edition advertisement's visual meaning and structure. This type of descriptive qualitative research uses Miles and Huberman analysis techniques, including reduction, presentation and drawing conclusions. Data sources through secondary data related to advertising, research methodology and the meaning contained in scientific works, books, the internet or websites. The research results show that the Rejoice 3in1 x Kiky Saputri #RambutNoDrama Rich Edition advertisement has a visual structure consisting of a main part, an explanatory part and a closing part. The environment, attire, title, bumper and digital elements like colors, scents, and video processing that give the impression that Kiky Saputri is speaking with the video editor all highlight the advertisement's visual meaning through interpretation.